Seeing White: Management of TIVA during autologous breast reconstruction. Issue 9 (September 2021) - Vigneswaran, Piranavhan; Clancy, Rachel; Choo, S.Y.; Love-Jones, Sarah; Jackson, Philippa C.; Wilson, Sherif M.
Summary: Total IntraVenous Anaesthesia is frequently the anaesthetic of choice for enhanced recovery after surgery pathways during breast reconstruction free flap surgery. This relies upon the continuous intravenous infusion of propofol. We describe our experience of two patients where augmentation of a venously congested DIEP flap with a cephalic vein transposition procedure, risked interruption of the intravenous delivery of anaesthesia to the patient. We also share our steps taken to mitigate this risk going forward.